Biofunctionalization of Polymers and their Applications - Nyanhongo, Gibson Stephen; Steiner, Walter; Gübitz, G. M. (Georg M.) (Advances in Biochemical Engineering / Biotechnology, 2011)
Chitin, Chitosan and Derivatives for Wound Healing and Tissue Engineering, by Antonio Francesko and Tzanko Tzanov; *Polyhydroxyalkanoates (PHA) and their Applications, by Guo-Qiang Chen; *Enzymatic Polymer Functionalisation: Advances in Laccase and Peroxidase Derived Lignocellulose Functional Polymers, by Gibson S. Nyanhongo, Tukayi Kudanga, Endry Nugroho Prasetyo and Georg M. Guebitz; *Lipases in Polymer Chemistry, by Bahar Yeniad, Hemantkumar Naik and Andreas Heise; *Enzymes for the Biofunctionalization of Poly(Ethylene Terephthalate), by Wolfgang Zimmermann and Susan Billig; *Biology of Human Hair: Know Your Hair to Control It, by Rita Araújo, Margarida Fernandes, Artur Cavaco-Paulo and Andreia Gomes; *Recombinamers: Combining Molecular Complexity with Diverse Bioactivities for Advanced Biomedical and Biotechnological Applications, by José Carlos Rodríguez-Cabello, María Pierna, Alicia Fernández-Colino, Carmen García-Arévalo and Francisco Javier Arias; *Biomimetic Materials for Medical Application Through Enzymatic Modification, by Piergiorgio Gentile, Valeria Chiono, Chiara Tonda-Turo, Susanna Sartori and Gianluca Ciardelli; *Supramolecular Polymers Based on Cyclodextrins for Drug and Gene Carrier Delivery, by Jia Jing Li, Feng Zhao and Jun Li; *Engineering Liposomes and Nanoparticles for Biological Targeting, by Rasmus I. Jølck, Lise N. Feldborg, Simon Andersen, S. Moein Moghimi and Thomas L. Andresen